Comparison of eye-lens doses imparted during interventional and non-interventional neuroimaging techniques for assessment of intracranial aneurysms. (27th February 2017) - Guberina, N; Dietrich, U; Forsting, M; Ringelstein, A
Abstract : Background: A neurointerventional examination of intracranial aneurysms often involves the eye lens in the primary beam of radiation. Objective: To assess and compare eye-lens doses imparted during interventional and non-interventional imaging techniques for the examination of intracranial aneurysms. Methods: We performed a phantom study on an anthropomorphic phantom (ATOM dosimetry phantom 702-D; CIRS, Norfolk, Virginia, USA) and assessed eye-lens doses with thermoluminescent dosimeters (TLDs) type 100 (LiF:Mg, Ti) during (1) interventional (depiction of all cerebral arteries with triple 3D-rotational angiography and twice 2-plane DSA anteroposterior and lateral projections) and (2) non-interventional (CT angiography (CTA)) diagnosis of intracranial aneurysms. Eye-lens doses were calculated following recommendations of the ICRP 103. Image quality was analysed in retrospective by two experienced radiologists on the basis of non-interventional and interventional pan-angiography examinations of patients with incidental aneurysms (n=50) on a five-point Likert scale. Results: The following eye-lens doses were assessed: (1) interventional setting (triple 3D-rotational angiography and twice 2-plane DSA anteroposterior and lateral projections) 12 mGy; (2) non-interventional setting (CTA) 4.1 mGy. Image quality for depiction of intracranial aneurysms (>3 mm) was evaluated as good by both readers for both imaging techniques. Conclusions: Eye-lens doses are markedly higher during the interventional than during the non-interventional diagnosis of intracranial aneurysms. For the eye-lens dose, CTA offers considerable radiation dose savings in the diagnosis of intracranial aneurysms.